¿Los estudiantes de bajo nivel de uso de estrategias son estudiantes de bajo rendimiento? - Samperio Sánchez, Nahum (Lenguas Modernas, 2019)
The purpose of this study is to identify the strategies that high achievers and low achievers have in common and how they use strategies. Quantitative data was collected through the Strategy Inventory for Language Learning (SILL). The qualitative data were gathered through ten individual semi-structured interviews. The general sample comprised 38 Low achievers and 19 High Achievers who belonged to the language center at a northern Mexican University. Data were analyzed with computer software Statistical Package for Social Sciences (SPSS) and Excel. Quantitative overall results indicate that there is not a significant difference in the frequency of strategy use between high achievers (HA) and low achievers (LA). However, a difference was found in Metacognitive and Memory strategies used by HA and LA. Findings also show a statistically significant difference in nine strategies of the questionnaire. In contrast, qualitative data shows that HA achievers use strategies more appropriately for their learning goals whereas LA use strategies less focused on their goals.